Особливості морфологічних та антропометричних показників студенток спеціальної медичної групи з низьким ростом - Бугаєвський, Костянтин Анатолійович; Бугаевский, К. А.; Bugaevskiy, K. A. (My University, 2016)
В останні десятиліття намітилася протилежна акселерації тенденція змін довжини тіла – відносне збільшення в репродуктивній когорті частки низькорослих жінок. Визначено, що ця студентська молодь є потенційною групою ризику стану репродуктивного здоров’я. Низький зріст жінки протягом багатьох років традиційно розглядається як фактор ризику акушерської та перинатальної патології. Актуальність дослідження зумовлена відсутністю відповідних даних про зміну цих показників у студенток з низьким зростом, які відносяться до спеціальної медичної групи. Мета роботи полягає у визначенні та аналізі отриманих індексних і антропометричних значень. В групі студенток з низьким зростом, були отримані наступні показники: середнє значення зросту в усій групі складає 158,88 ± 0,49 см. Зріст нижче середнього виявлено у 53,06 %, низький зріст встановлено в 44,9 %, дуже низький зріст у 2,04 % студенток. Підсумовуючи матеріал проведеного дослідження, можна констатувати, що в досліджуваній групі студенток спеціальної медичної групи з низькими показниками росту довжини тіла достовірно зафіксовані значні морфологічні та антропометричні зміни. Среди современной студенческой молодежи отмечаются различия антропометрических показателей и значений специальных индексов. В последние десятилетия на наметилась противоположная акселерации тенденция изменений роста – относительное увеличение в репродуктивной когорте доли низкорослых женщин. Эта студенческая молодежь является потенциальной группой риска состояния репродуктивного здоровья. Низкий рост женщины в течение многих лет традиционно рассматривается как фактор риска акушерской и перинатальной патологии. Актуальность исследования обусловлена отсутствием соответствующих данных об изменении этих показателей у студенток с низким ростом, которые относятся к специальной медицинской группе. Цель работы заключается в определении и анализе полученных индексных и антропометрических значений. В группе студенток с низким ростом, были получены следующие показатели: значение длины тела во всей группе составляет 158,88 ± 0,49 см. Рост ниже среднего (160-162 см) зафиксирован в 53,06 % студенток, низкий рост (150-159 см) установлено в 44,9 %, очень низкий рост у 2,04 %. В заключении можно констатировать, что в исследуемой группе студенток специальной медицинской группы с низкими показателями длины тела достоверно зафиксированы значительные морфологические и антропометрические изменения. Among the current students are marked differences in anthropometric parameters and values of specific indices. Relevance of the study due to the absence of relevant data on these indicators change in students with low growth, which belong to special medical group. Purpose is to identify and analysis of the index and anthropometric values. The low growth for many years, women traditionally considered as a risk factor for obstetric and perinatal pathology, mainly in the context of the imbalance of the pelvis of the mother and the fetal head, associated trauma, hypoxic complications. In domestic classification approaches to assess the degree of perinatal risk threshold height is 155 cm in foreign – 157 cm (according to the Institute of Medicine Criteria), which generally does not bear contradictions as common headings body length refers to the low growth of women 150-158 cm, with fluctuations of this indicator, depending on race and ethnic groups. So special importance of health research students as a special social group with a high risk of functional disorders of the body. Investigation of college-age young people necessary for timely measures of healthy and have great social significance. Young girls students are the future mothers, which depends on the health of future generations to come. In the study we have available scientific literature on the subject has been found sufficient amount of research devoted to the study of individual anatomical variability of the female body in youth and adulthood and the formation of various body systems, during the completion of the skeleton, complete growth of the body, puberty, willingness body to fulfill their reproductive function. Indicators of sexual, physical development (body weight and height, the associated value of special indexes) can be attributed to markers harmonious girls becoming reproductive system (Chernukha EA, 1991, Yakovlev EB, Iron RA, 1999; Nechitailo JM et al., 1999). Analyzing the results of anthropometric indices in the group of students with low stature, received the following indicators: growth in the average value of the entire group is 158,88 ± 0,49 cm. Minimum height in the group was 148 cm, the maximum – 165 cm. Height below average (160-162 cm) was found in 53,06 % of the «low» students of special medical group. Average growth in this group was 161 ± 0,24sm. The low height (150-159 cm) found in 44,9 % of the «low» students. Average growth in this group is 155 ± 1,34sm. Very low height (140-149 cm) was recorded at 2,04 % of the «low» students. Average growth is 145sm. During the investigation it was reliably established that somo asthenic type detected in 28,57 % of students, normostenic somo type – 24,49 % and hypersthenic somo type – 46,94 % of students.
Особенности морфологических и антропометрических показателей студенток специальной медицинской группы с низким ростом
Features morphological and anthropometric parameters of female students of special medical group With low growth
Keywords: студентки; антропометрія; низький зріст; індекси; репродуктивне здоров’я; спеціальна медична група; антропометрия; низкий рост; индексы; репродуктивное здоровье; специальная медицинская группа.; female students; anthropometry; low growth; indexes; reproductive health; special medical group